Special supplementary issue of the New Zealand Veterinary Journal: Bovine TB in New Zealand - Editors (New Zealand Science Review, 2015)
​This supplementary issue of the NZVJ is entirely focused on bovine tuberculosis (TB) in New Zealand, with a particular emphasis on controlling TB in wildlife. It brings together an extensive body of work describing the campaign to control bovine TB in New Zealand that commenced more than a century ago. The issue is introduced by an editorial by Professor Richard (Dez) Delahay, Wildlife Biologist at the National Wildlife Management Centre, Animal and Plant Health Agency, UK, who has worked extensively on the prevalence of TB in wild animals in the south-west of England. The subsequent articles include reviews by Paul Livingstone, from TBfree NZ, describing the evolution of TB control from an initial focus on cattle to national pest management strategies, targeted at controlling TB in possums. These strategies have resulted in the very real possibility that TB may be eradicated from both livestock and wildlife in New Zealand. Bryce Buddle, from AgResearch, reviews the management of TB in farmed cattle and deer, including diagnostic testing methods and movement controls, and looks forward to new techniques for investigating herd breakdowns. Two review papers by Graham Nugent, from Landcare Research, describe the epidemiology and control of Mycobacterium bovis infection in possums, and in wild deer and feral pigs. Also from Landcare Research, Andrea Byrom reviews the role of feral ferrets in potential transmission or risk pathways that have implications for management of TB, and Mandy Barron explores how multi-host dynamics may affect the prevalence of TB in other host species. Finally, there are reviews describing the main strategic, tactical and operational practices that have been developed, as well as integrated surveillance systems, for reducing or completely eliminating TB in wildlife, by Bruce Warburton and Dean Anderson, also of Landcare Research.